Research on the Speckle Effect Suppression Technology of a Laser Vibrometer Based on the Dual-Wavelength Detection Principle - Xiangyi Jin; Yangyi Shen; Yahao Wang; Xinxin Kong; Wenxi Zhang (Applied Sciences)
Laser vibrometers are known for their high precision, long-range capabilities, and non-contact measurement characteristics. However, in long-range applications, spike noise often arises, primarily due to the laser speckle effect induced by rough targets. To address this challenge, this paper develops a light field transmission model for laser vibrometers. By exploiting the differences in speckle patterns formed by lasers of different wavelengths on the same rough target, a dual-wavelength laser vibrometry technique utilizing wavelength division multiplexing devices is proposed, along with a dual-channel signal enhancement method based on orthogonal demodulation. This approach effectively reduces the likelihood of spike noise and enhances the system’s velocity measurement resolution. The experimental results demonstrate that, compared to the single-wavelength system, the dual-wavelength system significantly suppresses laser speckle noise, mitigates measurement spike noise, and improves the stability of micro-vibration measurements. Additionally, the system’s velocity resolution improves from 0.165 μm/s/Hz1/2 in the single-wavelength system to 0.122 μm/s/Hz1/2 in the dual-wavelength system, thereby enhancing the system’s sensitivity to micro-vibrations. In engineering applications, the dual-wavelength approach provides higher stability and resolution for micro-vibration signal measurements.